Stres rodzicielski matek dzieci z autyzmem - Banasiak, Anna (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
The aim of the research presented in this article was to determine the level of parental stress among mothers of autistic children. Thirty-nine mothers of autistic children, forty mothers of children with Down syndrome as well as forty mothers of children with developing normally took part in the study. We used the Questionnaire on Resources and Stress (QRS, designed by J. Holroyd) to assess the parental stress among families of developmentally delayed children or children with intellectual disabilities. The results of the study indicate that, comparing to mothers of children with Down syndrome and mothers of children developing well, mothers of autistic children are the ones who experience the highest level of parental stress. Potential sources of coping strategies among mothers of children that suffer from autism are associated with relatively low stress levels as a result of disharmony within the family, personal issues, the child’s health situation and financial problems.